Optimal Fair Scheduling in S-TDMA Sensor Networks for Monitoring River Plumes - Luque-Nieto, Miguel Ángel; Moreno-Roldán, José Miguel; Poncela-González, Javier; Otero-Roth, Pablo (Hindawi Publishing Corporation, 2016)
Underwater wireless sensor networks (UWSNs) are a promising technology to provide oceanographers with environmental data in real time. Suitable network topologies to monitor estuaries are formed by strings coming together to a sink node.This network may be understood as an oriented graph. A number of MAC techniques can be used in UWSNs, but Spatial-TDMA is preferred for fixed networks. In this paper, a scheduling procedure to obtain the optimal fair frame is presented, under ideal conditions of synchronization and transmission errors. The main objective is to find the theoretical maximum throughput by overlapping the transmissions of the nodes while keeping a balanced received data rate from each sensor, regardless of its location in the network. The procedure searches for all cliques of the compatibility matrix of the network graph and solves a Multiple-Vector Bin Packing (MVBP) problem. This work addresses the optimization problem and provides analytical and numerical results for both the minimum frame length and the maximum achievable throughput.
Keywords: Redes inalámbricas; Acústica submarina; Scheduling; Underwater Acoustic Sensor Networks